Inhibition of G Protein-Activated Inwardly Rectifying K+ Channels by Extracts of Polygonum persicaria and Isolation of New Flavonoids from the Chloroform Extract of the Herb - Lajter, Ildikó; Vasas, Andrea; Orvos, Péter; Bánsághi, Száva; Tálosi, László; Jakab, Gusztáv; Béni, Zoltán; Háda, Viktor; Forgo, Peter; Hohmann, Judit (Planta Medica, 2013)
The G protein-activated inwardly rectifying K+ channel-modulatory activities of Polygonum persicaria extracts were investigated by using an automated patch-clamp method, with the aim of identifying natural sources of promising ion channel-blocking compounds. The chloroform extract of the whole plant at 0.1 mg/mL exhibited high G protein-activated inwardly rectifying K+ channel-inhibitory activity. Fractionation of this extract by vacuum liquid chromatography on RP-silica gel resulted in 6 fractions, which were evaluated for G protein-activated inwardly rectifying K+ channel-modulatory activity. RP-HPLC of the most active fractions afforded the main compounds 1–4 in pure form and a mixture containing the minor constituents. The structures were identified by means of UV, HRMS, and advanced NMR methods as 3-O-senecioyl-isorhamnetin (1), 3-O-angeloyl-isorhamnetin (2), 5,3′,4′,5′-tetramethoxy-6,7-methylenedioxyflavone (3), and 3,5,3′,4′,5′-pentamethoxy-6,7-methylenedioxyflavone (4). Compounds 1–4 are new natural products, though 4 was reported earlier as a synthetic compound. Neither the individual, nor the combined application of compounds 1–4 modified the G protein-activated inwardly rectifying K+ channel activity. However, a marked G protein-activated inwardly rectifying K+ current-inhibitory effect was detected on use of the HPLC eluates containing the minor compounds. These results indicate the presence of electrophysiologically active agents among the minor compounds.
Keywords: Polygonum persicaria; Polygonaceae; flavone esters; GIRK channel